DNA markers for forage and livestock improvement - Tarawali, Shirley A.; Rege, J.E.O.; Hanotte, Olivier H.; Hanson, Jean (International Institute of Tropical Agriculture, 1999)
Genetic markers are being used by scientists worldwide in both animal and plant related breeding and Development efforts. The International Livestock Research Institute (ILRI) is a new institute formed in January 1995 by the amalgamation of the former ILCA (International Livestock Centre for Africa) and ILRAD (International Laboratory for Research on Animal Diseases). Considerable benefits have resulted from the interactions between different but related aspects of these two institutes. For example, research on ruminant genetics and forage resources throughout sub-Saharan Africa (formerly carried out by ILCA) has combined with molecular genetic expertise of ruminant health (formerly represented by ILRAD). This has created a considerable focus of expertise for the use of molecular markers for ruminant and forage improvement. ILRI is currently pursuing four major areas of research that involve the application of genetic marker analysis: (a) characterization of forage plant genetic resources, (b) forage quality selection and improvement, (c) characterization of ruminant genetic resources, and (d) animal health. The present article presents a summary of the current aspects of these four areas. Under the animal health topic are discussed tick-borne diseases, trypanosomiasis and genetics of trypanotolerance; and under the characterisation, bovine linkage maps and DNA marker characterization of bovine biodiversity are examined. A phylogenetic tree representing the genetic relationship between African cattle breeds is also presented.